IglF mediates type VI secretion system spike assembly and promotes Francisella virulence - Manon Degabriel; Esteban Guiot; Mélissa Marcotte; Coline Berthollier; Diane Soussan; Laure Bataille; Clémence Journeau; Adrien Ducret; Sarah Dayet; Amandine Mosnier; Amandine Martin; Virginie Gueguen-Chaignon; et al. (Proceedings of the National Academy of Sciences, 2026)
Type VI secretion systems (T6SSs) are widely distributed among Gram-negative bacteria, where they mostly act to promote bacterial warfare. Bacteria from the Francisella genus possess T6SSs that phylogenetically diverge from all other T6SSs and constitute the T6SSii subtype. Francisella tularensis, the agent of tularemia, relies on its T6SS to secrete effectors into host cells. Despite the key role of this nanomachine in Francisella virulence, the structure of T6SSii and the mechanism underlying its assembly are still poorly understood. Here, using Francisella novicida , we focused on understanding the structure and assembly of the spike, the most apical T6SS complex coupling effector delivery and membrane-puncturing activity. We solved the structure of the protein of unknown function, IglF, in complex with the N-terminal domain of IglG, the T6SSii PAAR protein. Interaction between IglF and IglG enabled the assembly of a mature T6SS spike complex both in Francisella and in a heterologous expression system. In contrast, disrupting IglF:IglG interactions prevented assembly of the PAAR protein with the central spike complex and invalidated T6SS assembly, as visualized by monitoring T6SS dynamics or secretion. Accordingly, IglF:IglG interactions were required for F. novicida virulence in vitro and in a mouse model of tularemia. Altogether, our findings shed light on the assembly mechanism of the Francisella T6SSii spike complex and its importance in virulence.